Pengaruh Status Gizi Terhadap Kecerdasan Balita Usia 4-5 Tahun Peserta PMT-P Diwilayah Puskesmas Bandaran Kabupaten Pamekasan - Mei Lestari Ika Widyyati (Wiraraja Medika : Jurnal Kesehatan, 2019)
Nutrition is a major requirement for toddlers. At the age of toddlers is one of the special target groups 1000 the first day of life, during this period there is a rapid growth and development and prone to nutritional deficiencies research approach by means of observational technique Sampling in this study using simple random sampling technique with a large sample is done with the method of sampling the probability of calculation result test of significance (sig.) result of 0.186 greater than 0.05 So that the balance there is no influence between the status of nutrition to the intelligence of children aged 4-5 years for participants PMT-P Keywords : Nutritional status, intelligence level, additional food recovery Program (PMT-P)